Effect of Aqueous Extract of Achyranthes aspera Leaves on Antiretroviral Drug-Induced Hepatotoxicity in Rats - Umaru, Isaac John; Udoh, Mary Athanasius; Akafa, Tensaba Andes; Oteng, Joseph; Akem, Ingwu Joseph; Ngbede, Ocheifa Mathew; Utioukpan, Ashaka Fidelis; Mijinyawa, Aboki Nwunuji; Ekup, Ogholo Ogholo (Darul Yasin Al Sys, 2025)
Achyranthes aspera leaves are believed to reverse drug resistance and increase the efficacy of current drugs. Achyranthes aspera leaves contain many secondary metabolites needed for the redressal of diseases and ailment. Thus, the ART-induced hepatotoxicity in rats. Methodology: Thirty (30) albino rats were divided into 5 groups of 6 each and treated as follows: Group A (no antiretroviral drugs, no extract); group B (antiretroviral drugs alone); group C (extract alone); group D (antiretroviral drug plus 40 mg/kg extract); group E (antiretroviral drug plus 80 mg/kg extract). All treatment lasted for twenty-eight days. Blood samples were collescted and serum ALT and AST determined using UV-spectrophotometer. The mean (± S.E.M) of data were calculated and further analysed for statistical significance using graph Pad Prism 5.0. Results: Mean serum ALT were 36.8 ± 20.24, 56.11 ± 6.12, 54.6 ± 24.18, 90.40 ± 11.14, 88.36 ± 13.10 and that of AST were 143.8 ± 20.24, 208.4 ± 16.13, 60.0 ± 24.18, 164.40 ± 11.14, 52.36 ± 16.14 for groups A, B, C, D, and E respectively. There was a statistically significant difference between the mean values of serum AST for group B and those for group C. However, there was no statistically significant difference between the ALT values for the test and control groups of rats (p value >0.999) Also, there was no statistically significant difference between the mean values of AST for group B and those of groups A, D, E. Conclusions: This extract at a higher concentration should add to the treatment of HIV in synergy with antiviral drugs, However, the extract shown no significant reduction of serum ALT and AST in ART treated rats.